Formação de defeitos topológicos em cristais líquidos nemáticos confinados em cascas nanoscópicas - Oliveira, Ellena Juliana Lins de (2017)
The emergence of topological defects in liquid crystals confined in curved geometries has attracted a remarkable interest over the past decade, due to the possibility of exploring them as an efficient mechanism to obtain self-organized colloidal structures. Nematic liquid crystal shells may constitute a feasible alternative to the designing of building blocks for possible micro and nanoscopic devices on the basis of new metamaterials, where atoms are replaced by colloids. In these building blocks, local frustrations in the orientation order behave as attractor sites for polymeric ligands, enabling that an effective interaction may take place among colloids surrounded by thin nematic shells. In this work, we present molecular simulation results of the director field and defect structures in nematic shells on spherocylindrical colloidal particles under conditions of degenerate planar anchoring. These simulations unveil that a pair +1/2 topological defects occurs at each pole of spherical cups, while a certain number of pairs of +1/2 and -1/2 defects also appears close to the edge of the spherical cups. Further, we show that such multivalent behavior can be suitably adjusted by applying a strong external field, depending on the relative direction of the external field and the long axis of the spherocylinder. We also discuss the case of nematic shell on colloidal particles containing regions with both negative and positive Gaussian curvatures, such as a dumbbell-shaped particle. Our results show that the Gaussian curvature of these surfaces plays a very important role in the number, strength, and spatial location of the topological defects. We provide a detailed description of the main mechanisms behind the emergence of a multivalent behavior in such systems, analyzing their potential as building blocks for tunable self-assembly structures.